FOREIGN BODIES OF THE LARYNX IN CHILDREN OF THE EARLY AGE - D. M. Mustafaev; V. M. Svistushkin (Неотложная медицинская помощь)
ABSTRACT. The authors present two clinical cases of foreign bodies of the larynx in young children. Peculiarity of the first case is rare finding of the foreign body in the larynx at the 7-month-old baby with quite large in the form as the plastic fragments of the pen cap. Peculiarity of the represented second case is rare finding of the foreign body in the larynx at the one-year-old child with enough big sizes as the fragment of an egg shell. Despite the large sizes of the aspirated objects and their localization at the level of the glottis of the larynx children breathed through the natural airway. The foreign bodies were removed through the natural way with the aid of direct laryngoscopy, avoiding complications.